Acid-Mediated Denitrogenation/Rearrangement/Coupling of Benzyl Azides with Triazolyl-Substituted Cycloalkanones - Che, Yang; Wang, Rui; Fu, Ying; Du, Zhengyin (Synlett, 2020)
Organic molecules containing α-triazolyl or β-amino cyclic ketone fragments have been individually proven to show good bioactivities and to be useful in asymmetric and pharmaceutical syntheses. A triflic acid-promoted simple and efficient method for the synthesis of unsymmetrical α-triazolyl-α′-(aminomethyl)cycloalkanones from benzyl azides and α-triazolylcycloalkanones has been developed. A series of unsymmetrical α,α′-disubstituted cycloalkanones were obtained with high syn-diastereoselectivity and up to 82% yield. Examination of the reaction mechanism showed that the benzyl azides undergo protonation, nitrogen elimination, rearrangement, and electrophilic attack by the enol forms of the cyclic ketones.
Keywords: amino ketones; benzyl azides; denitrogenation; rearrangement; azido-Mannich reaction